Effect of Blending Baobab and Neem Leaves Extract on Optical Band Gap Energy for Solar Cell Applications - Onsate, Wislay Nyangau; Mugwang’a, Fanuel Keheze; Karanja, Joseph Muna (European Journal of Applied Sciences, 2024)
The effect of blending bio-dye extracts from neem and baobab tree leaves on the optical bandgap energy has been investigated. The change in Eg in response to blending at 33%, 50% and 67% by volume of baobab to neem extract has been determined and explored using UV-Vis spectroscopy and Tauc’s approximation method. The individual bandgap energies for pure baobab and pure neem extracts were identified as ca. 1.65 eV and ca. 1.76 eV, respectively. The bandgap energies for the blends obtained were 1.718 eV for 1:1, 1.778 eV for 1:2, and 1.693 eV for 2:1 blend. This observed shift in bandgap energy signifies an enhancement in the optical characteristics of the resultant dyes. Consequently, the blended extracts exhibit superior optical absorption properties compared to their parent dyes, positioning them as more effective sensitizers for dye-sensitized solar cells. The findings underscore the potential of these blended bio-dye extracts in advancing the efficiency of solar cell technologies.